Black truffle ‐ associated bacterial communities during the development and maturation of T uber melanosporum ascocarps and putative functional roles - Sanjay Antony‐Babu; Aurélie Deveau; Joy D. Van Nostrand; Jizhong Zhou; François Le Tacon; Christophe Robin; Pascale Frey‐Klett; Stéphane Uroz (Environmental Microbiology, 2014)
Summary Although truffles are cultivated since decades, their life cycle and the conditions stimulating ascocarp formation still remain mysterious. A role for bacteria in the development of several truffle species has been suggested but few is known regarding the natural bacterial communities of P érigord B lack truffle. Thus, the aim of this study was to decipher the structure and the functional potential of the bacterial communities associated to the B lack truffle in the course of its life cycle and along truffle maturation. A polyphasic approach combining 454‐pyrosequencing of 16S rRNA gene, TTGE , in situ hybridization and functional G eo C hip 3.0 revealed that B lack truffle ascocarps provide a habitat to complex bacterial communities that are clearly differentiated from those of the surrounding soil and the ectomycorrhizosphere. The composition of these communities is dynamic and evolves during the maturation of the ascocarps with an enrichment of specific taxa and a differentiation of the gleba and peridium‐associated bacterial communities. Genes related to nitrogen and sulphur cycling were enriched in the ascocarps. Together, these data paint a new picture of the interactions existing between truffle and bacteria and of the potential role of these bacteria in truffle maturation.